Hollywood romantic comedy : states of the union, 1934-65 - Glitre, Kathrina (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2006)
Exploring the changing representation of the couple in romantic comedy and focusing on the key themes of marriage, equality and desire, this work analyses the discourses around heterosexuality, gender, romance and love.